2001
DOI: 10.1093/heapol/16.suppl_1.24
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of Health Workers for Change in seven settings: a useful management and health system development tool

Abstract: This paper presents the findings of a multi-centre study assessing the impact of Health Workers for Change (HWFC) workshops in seven different primary care sites, based on the common core protocol described in this paper. The paper discusses a common methodology used by the studies, consisting of a triangulation of qualitative and quantitative methods. Such methodologies are inherently complex as they require comparisons across systems, sites and procedures. The studies were conducted in six sites in Africa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 2 publications
0
33
0
Order By: Relevance
“…Studies have reported improvements in service provision and provider-client relations following training of healthcare providers on interpersonal and communication skills[50, 51]. This form of targeted training could improve providers’ self-awareness and sensitize them on how to better engage women during childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported improvements in service provision and provider-client relations following training of healthcare providers on interpersonal and communication skills[50, 51]. This form of targeted training could improve providers’ self-awareness and sensitize them on how to better engage women during childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting qualitative methods to ensure gender equity in healthcare and improving provider-client interaction and humanity of health services are still needed as recommended by many researchers. [27][28][29][30] The current study showed that physically abused women were significantly less likely to be covered by medical insurance. Only a small proportion of women: those working, of higher education, higher wealth index or older age cohorts were medically insured.…”
Section: Discussionmentioning
confidence: 99%
“…While the engagement of midwives improved, the majority of the doctors did not participate in the mentorship sessions. Iterative team engagement with data to identify problems and track progress on implementing local solutions is a hallmark of quality improvement cycles [22], but they also need to address organizational culture and norms that may inhibit frontline health workers' critical engagement and ability to implement the required changes [22,23].…”
Section: Pathways Of Changementioning
confidence: 99%